An introduction fo Christian ethics - Gilbride, Juliana (CCEA GCSE Religious Studies, 2018)
Comprehensively updated to address the revised CCEA GCSE specification for Religious Studies, this book covers Unit 6: 'An Introduction to Christian Ethics' of the specification. Full colour and illustrated throughout with questions, activities and extension activities.